Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1200/op.21.00658
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening Among Rural and Urban Clinics During COVID-19: A Multistate Qualitative Study

Abstract: PURPOSE: The effects of COVID-19 have been understudied in rural areas. This study sought to (1) identify cancer screening barriers and facilitators during the pandemic in rural and urban primary care practices, (2) describe implementation strategies to support cancer screening, and (3) provide recommendations. METHODS: A qualitative study was conducted (N = 42) with primary care staff across 20 sites. Individual interviews were conducted through videoconference from August 2020 to April 2021 and recorded, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Cancer screening could have been impacted by a number of federal, state, or local public health emergency policies, as well as by the changing priorities and capacities of health systems, and by individual social distancing behaviors (Cancino et al 2020; Richards et al 2020; DeJong, Katz, and Covinsky 2021). More recent research illuminated the role of financial stress and time costs as individual-level barriers to cancer screening, both of which may have compounded the strain on health systems attempting to resume cancer screening programs (Hanna et al 2022; Peoples et al 2022; Findling, Blendon, and Benson 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer screening could have been impacted by a number of federal, state, or local public health emergency policies, as well as by the changing priorities and capacities of health systems, and by individual social distancing behaviors (Cancino et al 2020; Richards et al 2020; DeJong, Katz, and Covinsky 2021). More recent research illuminated the role of financial stress and time costs as individual-level barriers to cancer screening, both of which may have compounded the strain on health systems attempting to resume cancer screening programs (Hanna et al 2022; Peoples et al 2022; Findling, Blendon, and Benson 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent research has found that in the later months of 2020, claims and records of cancer screenings returned to pre-pandemic levels (Chen et al 2021); DeGroff et al 2021; Labaki et al 2021; McBain et al 2021; Bello, Chang, and Massarweh 2022; Drescher et al 2022). Still, the pandemic created a major cancer screening deficit which may be difficult to address despite recent investment in “return to screening” initiatives (Chen et al 2021; Hanna et al 2022; Kelkar et al 2022). Even as America returns to screening, some are being left behind (Mafi et al 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contextual factors (eg, stay-at-home orders), organizational factors (eg, prioritizing response to acute illness), and/or patient-level factors (eg, fear of contracting COVID-19) likely explain the evidence that shows that fewer people received breast, cervical (CVC), and colorectal (CRC) cancer screenings during the COVID-19 timeframe 2–7 . Early evidence suggests better recovery for CRC than CVC screenings 5 . But these studies are limited in scope as they focus on one health center, a single state, or a specific program 8–12 .…”
mentioning
confidence: 99%
“…But these studies are limited in scope as they focus on one health center, a single state, or a specific program 8–12 . And, very few existing studies have examined how cancer screening rates have recovered 5 . Early evidence suggests better recovery for CRC than CVC screenings, though it is unknown what factors or strategies contributed to this recovery 5 …”
mentioning
confidence: 99%